Pengaruh Komunikasi Kerja dan Pelatihan Terhadap Kinerja Pegawai pada Pusat Kebijakan Sistem Ketahanan Kesehatan dan Sumber Daya Kesehatan di Kementerian Kesehatan Republik Indonesia - Winarsih Winarsih; Bambang Nurakhim; Siti Ubaydah (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
The pupose of the research is as follows To find out whether partially or jointly there is influence between Work Communication and Training on employee performance at the Center for Health Resilience and Health Resources Policy at the Ministry of Health of the Republic of Indonesia. The sampling technique used in this research, the author used the Total Random Sampling technique. The positive influence of work communication on employee performance is obtained by a partial value of 0.899, meaning there is a very strong influence or an influence with a coefficient of determination of 80.8%. There is a positive influence of training on employee performance, a partial value of 0.869 is obtained, meaning there is a very strong influence or an influence with a coefficient of determination of 69.3%. Simultaneously the positive influence of the Work Communication and Training variables on the Employee Performance variable with a simultaneous correlation value or Summary Model produces an R value of 0.855 while the R Square value is 0.731 or 73.1%, this can be stated that the results of the analysis together Work Communication and Training variables on Employee Performance variables have a very strong influence. Proven through the results of the F test (ANOVA) or Fcount, a value of 18.378 was obtained, which is greater than Ftable (50) of 2.790 with a significant level of 0.000, so it can be said that the Work Communication and Training variables together or Simultaneously, there is a significant influence on employee performance. In conclusion, there is an influence of work communication and training on team member performance at the center of health resilience system policies and health resources Keywords: Performance. Training, Work Communication